Self-assembled porous nanosheet structure ZnO catalyst and its preparation method and application
Synthesizing self-assembled nanosheet structure ZnO catalyst by chemical precipitation method solves the problems of low energy consumption and high efficiency of the existing ethylene production process, achieves excellent catalytic effect in CO2 atmosphere, and improves the activity and selectivity of the catalyst.
Patent Information
- Application Number
- CN202211045866.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-08-29
AI Technical Summary
The existing ethylene production process has problems of low energy consumption and high efficiency, and the ethane oxidation and dehydrogenation catalyst has low activity and has defects such as non-selective oxidation.
The self-assembled nanosheet structure ZnO catalyst was synthesized by chemical precipitation method, and materials such as zinc acetate and ammonium carbonate were aged under specific conditions to form a porous nanosheet structure, which increased the specific surface area and alkaline strength of the catalyst.
The excellent catalytic effect in the dehydrogenation and ethylene reaction of ethane oxide in CO2 atmosphere is achieved, which improves the activity and selectivity of the catalyst and is suitable for large-scale production.
Smart Images

Figure CN115999531B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a self-assembled nanosheet structure ZnO catalyst and a preparation method and application thereof. Background Art
[0002] Ethylene is widely used in the petrochemical industry. Nowadays, ethylene is indispensable in all fields of society. In 2018, the global demand for it reached 164 million tons, and its demand is expected to continue to grow at about 4% per year. However, the main process of ethylene production still has shortcomings, and it is urgent to explore and develop a low-energy and efficient ethylene production process. At the same time, with the maturity of natural gas exploration and production technology, large-scale shale gas reserves have been discovered worldwide. In this context, how to effectively utilize ethane catalytic conversion into corresponding high-value-added substances has become a research hotspot in recent years.
[0003] However, the main problem facing this reaction is how to prepare a catalyst that can efficiently catalyze the conversion of ethane. Currently, the activity of ethane oxidative dehydrogenation catalysts is low and has some defects. For example, when there are too many electrophilic oxygen species on the surface of NiO catalyst, non-selective oxidation is likely to occur.
[0004] As a semiconductor oxide material, zinc oxide has attracted more and more research attention due to its high catalytic activity, non-toxicity, abundant availability, and low cost. When the particles of zinc oxide are limited to nanometer size, nano zinc oxide shows special properties that bulk materials do not have. It is an important multifunctional inorganic oxide material with broad application prospects in many fields. In different growth environments, different crystal faces of zinc oxide have different growth rates. The growth of the crystal face can be controlled by changing certain parameters, thereby preparing zinc oxide with different morphologies, changing its chemical properties, and improving the catalytic performance of ZnO catalysts. Summary of the invention
[0005] The main purpose of the present invention is to provide a self-assembled porous nanosheet structure ZnO catalyst and a preparation method and application thereof, so as to overcome the deficiencies existing in the prior art.
[0006] To achieve the aforementioned object of the invention, the technical solution adopted by the embodiment of the present invention includes:
[0007] The embodiment of the present invention provides a method for preparing a self-assembled nanosheet structure ZnO catalyst, comprising:
[0008] Fully dissolve zinc acetate in water to form a zinc salt solution;
[0009] Dissolving the precipitant in water to form an alkaline solution;
[0010] Add the alkaline solution dropwise into the zinc salt solution and react at 70-75°C for 14-16 minutes, then allow to stand for aging;
[0011] After aging, the self-assembled nanosheet structured ZnO catalyst was obtained through filtration, washing, drying and calcination.
[0012] Furthermore, the concentration of zinc acetate in the zinc-containing salt solution is 0.02-0.021 g / ml.
[0013] Furthermore, the concentration of the alkaline solution is 0.030-0.031 g / ml.
[0014] Furthermore, the preparation method of the self-assembled nanosheet structured ZnO catalyst comprises: dripping an alkaline solution into a zinc salt solution in an oil bath at a dropping rate of 3-3.05 ml / min at 70-75° C., stirring at a stirring rate of 100-150 rpm, and condensing and refluxing. After the reaction, stopping stirring and standing for aging for 72±0.1 h.
[0015] Furthermore, the volume ratio of the alkaline solution to the salt solution is 1-1.05:1.
[0016] The embodiment of the present invention further provides a self-assembled nanosheet structure ZnO catalyst prepared by the above method. The thickness of the self-assembled nanosheet structure ZnO catalyst is 20-25 nm and the diameter is 50-100 nm.
[0017] The embodiment of the present invention also provides the use of the aforementioned self-assembled nanosheet structure ZnO catalyst for selective oxidation of ethane to produce ethylene by dehydrogenation in a CO2 atmosphere.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention synthesizes the nanosheet structured ZnO catalyst by chemical precipitation method, the preparation method is simple, the repeatability is good, and it can be mass-produced. In addition, the obtained nanosheet structured ZnO catalyst has good chemical stability and is easy to preserve.
[0020] (2) The nanosheet structured ZnO catalyst prepared by the present invention has a nanosheet structure that can provide a high specific surface area, enhance the basic strength of the catalyst, increase the number of surface basic sites, provide more high-activity sites, and produce an excellent catalytic effect in the selective oxidation of ethane dehydrogenation to ethylene in a CO2 atmosphere. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1a-1d These are scanning electron microscope images of the nanosheet structured ZnO catalyst of Example 1 at different aging times.
[0023] Figure 2a-2b This is a projection electron microscope image of the nanostructured ZnO-A-1 and ZnO-A-4 catalysts of Example 1.
[0024] Figure 3 CO2-TPD diagram of nanosheet structured ZnO catalyst at different aging times in Example 1.
[0025] Figure 4 This is a diagram showing the catalytic effect of the nanosheet structured ZnO catalyst of Example 1 at different aging times.
[0026] Figure 5 Schematic diagram of the catalytic effect of ZnO catalysts prepared from different zinc sources.
[0027] Figure 6 This is a diagram showing the catalytic effects of ZnO catalysts prepared with different precipitants. DETAILED DESCRIPTION
[0028] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The present invention synthesizes nanoparticle ZnO by a precipitation method, and then uses acetate as a structure-directing agent to age it for a certain period of time under certain temperature conditions. After washing with deionized water and drying, a self-assembled nanosheet structure ZnO catalyst with good chemical stability and easy preservation is obtained.
[0029] One aspect of an embodiment of the present invention provides a method for preparing a self-assembled nanosheet structure ZnO catalyst, comprising:
[0030] Fully dissolve zinc acetate in water to form a zinc salt solution;
[0031] Dissolving the precipitant in water to form an alkaline solution;
[0032] Add the alkaline solution dropwise into the zinc salt solution and react at 70-75°C for 14-16 minutes, then allow to stand for aging;
[0033] After aging, the self-assembled nanosheet structured ZnO catalyst was obtained through filtration, washing, drying and calcination.
[0034] In some preferred embodiments, the method for preparing the self-assembled nanosheet structured ZnO catalyst comprises: dissolving zinc acetate in deionized water, transferring the mixture into an oil bath, and stirring the mixture for 14-16 minutes at 70-75° C. and under condensation reflux conditions to fully dissolve the zinc acetate and form a zinc salt solution.
[0035] In some preferred embodiments, the concentration of zinc acetate in the zinc-containing salt solution is 0.02-0.021 g / ml.
[0036] In some preferred embodiments, the precipitant may include any one of ammonia water, sodium carbonate, ammonium carbonate, etc., but is not limited thereto.
[0037] In some more preferred embodiments, the precipitant is ammonium carbonate.
[0038] In some preferred embodiments, the concentration of the alkaline solution is 0.030-0.031 g / ml.
[0039] In some preferred embodiments, the method for preparing the self-assembled nanosheet structured ZnO catalyst comprises: dripping an alkaline solution into a zinc salt solution in an oil bath at a dropping rate of 3-3.05 ml / min at 70-75°C, stirring at a stirring rate of 100-150 rpm, and condensing and refluxing. After the reaction, stirring is stopped, and the mixture is allowed to stand for aging for 72±0.1 h.
[0040] In some preferred embodiments, the volume ratio of the alkaline solution to the salt solution is 1-1.05:1.
[0041] In some preferred embodiments, the calcination conditions are as follows: the sample is placed in a muffle furnace, heated to 500±10°C at a heating rate of 10±1°C / min, and then maintained at 500±10°C for calcination for 3±0.1h.
[0042] Another aspect of the embodiments of the present invention provides a self-assembled nanosheet structure ZnO catalyst prepared by the above method, wherein the thickness of the self-assembled nanosheet structure ZnO catalyst is 20-25 nm and the diameter is 50-100 nm.
[0043] Another aspect of the embodiments of the present invention further provides the use of the aforementioned self-assembled nanosheet structure ZnO catalyst for selective oxidation of ethane to produce ethylene by dehydrogenation in a CO2 atmosphere.
[0044] The nanosheet-structured ZnO catalyst prepared in the embodiment of the present invention has a porous nanosheet structure that can provide a high specific surface area, enhance the basic strength of the catalyst, increase the number of surface basic sites, provide more highly active sites, and produce an excellent catalytic effect in the selective oxidation of ethane dehydrogenation to ethylene in a CO2 atmosphere.
[0045] The preparation method of the self-assembled nanosheet structure ZnO catalyst of the present application is further described below with specific examples.
[0046]
[0047] Example 1
[0048] In this example, zinc acetate is used as the zinc source. 1g of zinc acetate is dissolved in 50ml of deionized water, transferred to an oil bath, and stirred rapidly at 70°C and under condensation reflux conditions to fully dissolve the zinc acetate as a zinc salt solution. 1.53g of ammonium carbonate is added to 50ml of deionized water and stirred rapidly to fully dissolve it as an alkaline solution. The alkaline solution is dripped into the salt solution in the oil bath at 70°C, while maintaining rapid stirring and condensation reflux. After 15 minutes, the stirring is stopped, and the catalyst is aged at 70°C for 0h, 24h, 48h or 72h. After turning off the temperature control and cooling to room temperature, the catalyst is taken out and filtered, washed, dried and calcined to finally obtain self-assembled nanosheet structure ZnO-A-1, ZnO-A-2, ZnO-A-3 and ZnO-A-4 catalysts.
[0049] Example 2
[0050] In this example, zinc acetate is used as the zinc source. 1g of zinc acetate is dissolved in 50ml of deionized water, transferred to an oil bath, and stirred rapidly at 70°C and under condensation reflux conditions to fully dissolve the zinc acetate as a zinc salt solution. 1.75ml of ammonia water is dissolved in 50ml of deionized water and stirred rapidly to fully dissolve it as an alkaline solution. The alkaline solution is dripped into the salt solution in the oil bath at 70°C, while maintaining rapid stirring and condensation reflux. After 15 minutes, the stirring is stopped, and after cooling to room temperature, the catalyst is taken out and filtered, washed, dried and calcined to finally obtain a self-assembled nanosheet structure ZnO-A-1-NH4OH catalyst.
[0051] Example 3
[0052] In this example, zinc acetate is used as the zinc source. 1g of zinc acetate is dissolved in 50ml of deionized water, transferred to an oil bath, and stirred rapidly at 70°C and under condensation reflux conditions to fully dissolve the zinc acetate as a zinc-containing salt solution. 1.10g of sodium carbonate is dissolved in 50ml of deionized water and stirred rapidly to fully dissolve it as an alkaline solution. The alkaline solution is dripped into the salt solution in the oil bath at 70°C, while maintaining rapid stirring and condensation reflux. After 15 minutes, the stirring is stopped, and after cooling to room temperature, the self-assembled nanosheet structure ZnO-A-1-Na2CO3 catalyst is finally obtained after filtration, washing, drying and calcination.
[0053] Comparative Example 1
[0054] In this example, zinc nitrate is used as the zinc source. 1.23g of zinc nitrate is dissolved in 50ml of deionized water, transferred to an oil bath, and stirred rapidly at 70°C and under condensation reflux conditions to fully dissolve the zinc nitrate as a salt solution. 1.53g of ammonium carbonate is dissolved in 50ml of deionized water and stirred rapidly to fully dissolve it as an alkaline solution. The alkaline solution is dripped into the salt solution in the oil bath at 70°C, while maintaining rapid stirring and condensation reflux. After 15 minutes, the stirring is stopped, and after cooling to room temperature, the catalyst is taken out and filtered, washed, dried and calcined to finally obtain a self-assembled nanosheet structure ZnO-Zn(NO3)2 catalyst.
[0055] Comparative Example 2
[0056] In this example, zinc chloride is used as the zinc source. 0.62g of zinc chloride is dissolved in 50ml of deionized water, transferred to an oil bath, and stirred rapidly at 70°C and under condensation reflux conditions to fully dissolve the zinc chloride as a salt solution. 1.53g of ammonium carbonate is dissolved in 50ml of deionized water and stirred rapidly to fully dissolve it as an alkaline solution. The alkaline solution is dripped into the salt solution in the oil bath at 70°C, while maintaining rapid stirring and condensation reflux. After 15 minutes, the stirring is stopped, and after cooling to room temperature, the catalyst is taken out and filtered, washed, dried and calcined to finally obtain a self-assembled nanosheet structure ZnO-ZnCl2 catalyst.
[0057] Catalytic performance test:
[0058] The ZnO catalyst was tested for CO2-ODHE catalytic performance in a constant pressure flow fixed bed reactor (id18mm), and a thermocouple was used to monitor the catalyst bed temperature. Normally, each test was performed with 200mg of catalyst as the standard. Quartz wool was placed in a quartz tube as a support carrier for the catalyst in the quartz tube, and then the weighed catalyst was poured into it, and then a small amount of quartz wool was covered on the catalyst to prevent the catalyst powder from being blown away during ventilation. After the above steps were followed, the quartz tube was moved into the fixed bed reactor for catalytic performance testing.
[0059] First, the fixed bed reactor was heated to 873K at a heating rate of 10K / min under N2 (30ml / min) atmosphere. Subsequently, the fixed bed temperature was maintained at 873K, and C2H6, CO2 and N2 were introduced into the reactor in a ratio of 1:1:2 (total flow rate = 60ml / min) for 5 hours. The composition of the reaction gas products (N2, CO, CH4, C2H4, CO2 and C2H6) was analyzed by an online gas chromatograph (GC-2000, equipped with a Porapak N column and a thermal conductivity detector). Before the reaction gas products entered the gas chromatograph, the moisture was removed by a desiccant.
[0060] The effect of different aging time on the morphology, such as Figure 1a-1d The figures are scanning electron microscope images of self-assembled nanosheet structures ZnO-A-1, ZnO-A-2, ZnO-A-3 and ZnO-A-4 catalysts at different aging times. As the aging time increases, small particles gradually accumulate and grow, and the ZnO-A-2 catalyst precursor forms a basis for the flaky structure. Subsequently, the ZnO-A-3 catalyst precursor generates an obvious flaky structure. In the final ZnO-A-4, the catalyst precursor presents a dense flaky structure.
[0061] Example 1 Projection electron microscopy images of nanostructured ZnO-A-1 and ZnO-A-4 catalysts, as shown in Figure 2a and Figure 2b As shown, Figure 2a The ZnO-A-1 catalyst is composed of amorphous particles. Figure 2b Some black stripes can be clearly seen in the ZnO-A-4 catalyst, indicating the presence of flake particles, and the morphological changes are consistent with the SEM results.
[0062] The relatively low peak is attributed to the desorption of CO2 adsorbed on the weakly basic sites on the catalyst surface, and the second peak at 673K-923K is attributed to the desorption of CO2 chemically adsorbed on the strongly basic sites. Figure 3 It can be seen that with the increase of aging time, different catalysts have different basic sites. There are both weak and strong basic sites in ZnO-A-1 catalyst, but the number is small; the weak basic sites on the surface of ZnO-A-2 catalyst disappear, but the strong basic sites increase; both exist on the surface of ZnO-A-3 catalyst, but their number increases significantly; there are a large number of strong basic sites on the surface of ZnO-A-4 catalyst, and the weak basic sites almost disappear.
[0063] Figure 4 The ethane conversion rate gradually increased with the increase of catalyst aging time, from the initial 7.95% to 12.94%. The activation ability of ZnO-A-4 for ethane was significantly higher than that of the unaged catalyst, indicating that with the increase of aging time, the number of high-activity sites increased significantly, but these sites were more prone to ethane over-oxidation, so the selectivity of the catalyst gradually decreased.
[0064] The catalysts were prepared using different precursors and the corresponding research was carried out. Figure 5 As shown in the figure, the catalyst prepared with zinc acetate as the precipitant has the best effect, and by adding acetic acid during the preparation of zinc nitrate, it can be seen that the presence of AC has a greater influence on the catalytic effect of ZnO catalyst. Combined with the literature, it can be seen that this may be because AC will hinder the growth of ZnO particles in the c-axis direction when they are formed, thereby having a certain impact on the catalytic effect.
[0065] The catalysts were prepared using different precipitants and the corresponding investigations were carried out. Figure 6 As shown in the figure, the catalyst prepared with ammonium carbonate as the precipitant has the best effect. Compared with the catalytic effects of sodium carbonate and ammonia water as precipitants, it can be seen that carbonate has a greater influence on the activity of the catalyst. After calcination in a muffle furnace, the carbonate in the catalyst precursor will be discharged in the form of CO2 gas, thereby forming a porous structure on the catalyst surface. The formation of this structure may be conducive to the exposure of the active sites of the catalyst, thereby greatly affecting the activity of the catalyst.
[0066] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0067] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.
Claims
1. Application of a self-assembled nanosheet structure ZnO catalyst in selective oxidation of ethane dehydrogenation to ethylene in a CO2 atmosphere, wherein the preparation method of the self-assembled nanosheet structure ZnO catalyst comprises: Fully dissolving zinc acetate in water to form a zinc salt solution; Dissolving the precipitant in water to form an alkaline solution; Add the alkaline solution dropwise into the zinc salt solution and react at 70-75°C for 14-16 minutes, then allow to stand for aging; After aging, the catalyst is filtered, washed, dried and calcined to obtain a self-assembled nanosheet structure ZnO catalyst, wherein the thickness of the self-assembled nanosheet structure ZnO catalyst is 20-25 nm and the diameter is 50-100 nm.
2. The use according to claim 1, characterized in that: The preparation method of the self-assembled nanosheet structure ZnO catalyst comprises: dissolving zinc acetate in deionized water, transferring the mixture into an oil bath, and stirring the mixture for 10-15 minutes at 70-75° C. and under condensation reflux conditions to fully dissolve the zinc acetate and form a zinc salt solution.
3. The use according to claim 1 or 2, characterized in that: The concentration of zinc acetate in the zinc salt solution is 0.02-0.021 g / mL.
4. The use according to claim 1, characterized in that: The precipitant is selected from any one of ammonia water, sodium carbonate or ammonium carbonate.
5. The use according to claim 4, characterized in that: The precipitant is ammonium carbonate.
6. The use according to claim 1, characterized in that: The concentration of the alkaline solution is 0.030-0.031 g / mL.
7. The use according to claim 6, characterized in that: The preparation method of the self-assembled nanosheet structure ZnO catalyst comprises: dripping an alkaline solution into a zinc salt solution in an oil bath at a dropping rate of 3-3.05 mL / min at 70-75° C., stirring at a stirring rate of 100-150 rpm, and condensing and refluxing. After the reaction, stirring is stopped, and the solution is allowed to stand for aging for 72±0.1 h.
8. The use according to claim 1 or 7, characterized in that: The volume ratio of the alkaline solution to the salt solution is 1-1.05:
1.
9. The use according to claim 1, characterized in that: The calcination conditions are as follows: the sample is placed in a muffle furnace, heated to 500±10°C at a heating rate of 10±1°C / min, and then maintained at 500±10°C for calcination for 3±0.1h.